Mean-field analysis of the ising hysteresis relaxation time - Yongyut Laosiritaworn (2018)
In this work, the mean-field analysis was used to model Ising spins under the influence of time-oscillating magnetic field. The magnetic hysteresis was extracted by solving the non-linear differential equation of the magnetization in response to the field. The dynamic order parameter and its relaxation time were investigated as a function of temperature and characteristic of the field. From the results, it was found that the dynamic order parameter decayed in time and converged to zero or nonzero values depending on temperature, the magnetic field frequency and amplitude. The relaxation time was found to be small at high temperatures and fields, but increasing on approaching the dynamic phase boundaries. Furthermore, the relaxation time increased with increasing field frequencies due to the shift of the dynamic phase boundary as varying the frequencies. The detailed description to these phenomena can be explained by considering the dynamic phase diagram on the temperature and field amplitude plane for various field frequencies.